Experimental Validation of the Tyndall Portable Lower-limb Analysis System with Wearable Inertial Sensors. (2016) - Tedesco, Salvatore; Urru, Andrea; Clifford, Amanda; O'Flynn, Brendan
Abstract: Biomechanical analysis of movement during sport practice is extremely useful to assess and, subsequently, optimise movement performance during sport which can also assist athletes during rehabilitation following injury (such as Anterior Cruciate Ligament reconstruction). It is mostly performed using camera-based motion analysis systems, which provide good results but present serious drawbacks (for instance, consistent size, high cost, and lack of portability). Thus, small-size low-cost wearable sensors are an emerging tool for biomechanics monitoring. Aim of the present work is to implement a novel wireless portable easy-to-use system, consisting of two Tyndall Wireless Inertial Measurement Units (WIMUs) per leg, suitable for free-living environments and able to provide a complete biomechanics assessment (generated on a report) without the constraints of a laboratory. Validation for the lower-limbs using state-of-the-art camera-based motion capture is presented here. Algorithms are implemented in Matlab, and the scenarios considered simulate a free-living environment and exercises performed in a rehabilitation procedure. The system has been validated with healthy and impaired subjects. This novel system shows high accuracy values for all considered scenarios. Moreover, it is able to detect atypical movement characteristics. The results of this feasibility study support the next phase which will be to assess the external and ecological validity of athletes' on-field movement performance, which will help to inform individualised training protocols or enhance targeted rehabilitation programmes.